The role of MCT1 in tumor progression and targeted therapy: a comprehensive review - Xu, Zheng; Wang, Xuemei; Cheng, Hongjing; Li, Jiuling; Zhang, Xin; Wang, Xueju (Frontiers in Immunology, 2025)
Overexpression of monocarboxylate transporter 1 (MCT1) in tumor cells is often associated with poor prognosis. The established mechanisms through which MCT1 and its mediated lactate transport drive tumor progression are manifold. The classical mechanisms include fostering metabolic symbiosis among tumor cells, dampening the immune function of immune cells, and spurring tumor angiogenesis. Beyond these, new findings of MCT1’s role in tumor progression have emerged. These new findings highlight MCT1’s involvement in mediating the reverse Warburg effect, inhibiting ferroptosis, promoting protective autophagy, and augmenting tumor glycolysis. When acetate serves as a transport substrate for MCT1, additional mechanisms come into play. These encompass MCT1’s participation in the acetylation of histone H3K27 and its role in upregulating c-Myc levels. Several studies have demonstrated that while selective MCT1 inhibitors can effectively impede tumor progression, they also face notable challenges. To address these, combining MCT1 inhibitors with other drugs appears to hold more promise.